Atoms - O'Mara, Kennon (Look at chemistry., 2019)
Provides young learners with basic information on the properties of atoms, how atoms make up elements on the periodic table, and diagrams of the atomic makeup of particular elements. Includes diagrams, photographs, a glossary, and an index.